2023
DOI: 10.3389/fpubh.2023.1129056
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice of healthcare workers regarding dengue fever in Mazandaran Province, northern Iran

Abstract: BackgroundDengue fever is a rapidly emerging infection worldwide with a high public health burden. Adequate training of healthcare workers is essential to warrant the timely provision of health services to improve the outcome of dengue management.MethodsThis is an analytical cross-sectional study, conducted to assess the knowledge, attitudes and practice (KAP) of healthcare workers regarding dengue from April 2021 to March 2022 in Mazandaran Province, northern Iran. Data was collected using a researcher-made s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
(47 reference statements)
3
10
0
Order By: Relevance
“…In this study, the highest percentage of lack of knowledge was related to the dimensions of prevention (88.6%) and transmission (77.4%), which was consistent with Ho's study [32]. In another study conducted in Mazandaran, Iran, HCPs had higher knowledge associated with the transmission, clinical management, and prevention and control of dengue as compared with the results of our study [37]. This difference may be due to the non-endemic nature of DF…”
Section: Plos Onesupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the highest percentage of lack of knowledge was related to the dimensions of prevention (88.6%) and transmission (77.4%), which was consistent with Ho's study [32]. In another study conducted in Mazandaran, Iran, HCPs had higher knowledge associated with the transmission, clinical management, and prevention and control of dengue as compared with the results of our study [37]. This difference may be due to the non-endemic nature of DF…”
Section: Plos Onesupporting
confidence: 91%
“…Therefore, considering the report of the presence of Aedes aegypti and Aedes albopictus in the country [13,14] with a high risk of spreading throughout the country causing outbreaks and epidemics of arboviruses including dengue, it seems necessary to improve the knowledge of the HCPs by whatever means possible including but not limited to holding educational workshops, distributing posters and pamphlets in health and treatment centers, social media and etc. Similar to the findings of this research (13.3%), in Khan's study (13.3%) a low percentage of the participants were aware of the daytime biting habit of the dengue vectors [43] while in other studies, this proportion was quite different [25,37,39]. This misapprehension may lead healthcare providers to give patients incorrect preventive counsel.…”
Section: Plos Onesupporting
confidence: 79%
“…Divergent results were found across different studies in the literature. Higher rates of correct answers were reported in Ethiopia, Iran, and Ecuador, with percentages of 79% (Mohammed Yusuf and Abdurashid Ibrahim, 2019), 75.7% (Nikookar et al, 2023), and 75% (Handel et al, 2016) respectively. In contrast, lower percentages were found in a study in Taiwan 27.1% (Huang et al, 2011).…”
Section: Discussionmentioning
confidence: 89%
“…For comparison, Yusuf and colleagues identified that in Ethiopia in 2019, 48% of surveyed healthcare workers exhibited appropriate dengue-related practices based on a 60% cut-off ( 29 ). Similarly, using a 70% cut-off, Nikookar et al reported that in Iran in 2023, an impressive 73.0% of participants had good practices ( 38 ). The scant proportion of adequate dengue practices in our study could primarily be attributed to the reported unavailability of dengue diagnostic equipment within the participants' health region.…”
Section: Discussionmentioning
confidence: 99%